Synergistic androgenic effect of a petroleum product caused by the joint action of at least three different types of compounds. - Jonker, M.; Candido, A.; Vrabie, C.; Scarlett, Alan; Rowland, S. (2015)
In a previous study, we found a dose-dependent synergistic effect in recombinant yeast stably transfected with the human androgen receptor (AR), in response to co-exposure to testosterone and a commercially-available lubricant (engine) oil for cars. As there is relatively little knowledge on synergistic toxic effects and causative compounds, particularly for the androgenic system, the objective of the present study was to investigate this oil in more detail. The oil was fractionated into SARA fractions (so-called 'saturates', 'aromatics', 'resins', and 'asphaltenes') by open column chromatography. Surprisingly, when exposing the recombinant AR yeast to testosterone in combination with the separate SARA fractions, the synergistic effect could not be reproduced fully. After pooling the fractions again however, the full synergism returned. From subsequent exposures to combinations of two or three SARA fractions, it appeared that both the 'saturates' and the 'resins' fraction were required for obtaining the synergistic response with testosterone. This clearly demonstrates a synergistic effect related to the androgenic system caused by the joint action of at least three chemically-distinct compounds, or groups of compounds (i.e. testosterone, 'resins' and 'saturates'). Although detailed chemical analyses could not reveal the identity of the causative compounds and the in vivo relevance of the present results remains unclear, the results do add to the growing body of evidence on the potentially extremely complex character of mixture effects.